(untitled) (Journal of Nepal Physical Society, 2019)
We have present properties like inclination angle, dust color temperature and dust mass of core region in far infrared located nearby White dwarf WD2236+541.The size of cavity is 0.84 pc×0.51 pc. The cavity is formed by high pressure at the time of white dwarf formation. The dust color temperature varies from 22.42K to 27.43 K. The inclination angle of cavity is 54.2°. The position of white dwarf is found at R.A. J (2000)= 22h38m24s and Dec. J (2000)= +54°26m19s.